The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/livers1040021
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs Interactions in Hepatic Stellate Cells during Hepatic Fibrosis

Abstract: Hepatic fibrosis is a reversible wound healing process following liver injury. Although this process is necessary for maintaining liver integrity, severe excessive extracellular matrix accumulation (ECM) could lead to permanent scar formation and destroy the liver structure. The activation of hepatic stellate cells (HSCs) is a key event in hepatic fibrosis. Previous studies show that most antifibrotic therapies focus on the apoptosis of HSCs and the prevention of HSC activation. Noncoding RNAs (ncRNAs) play a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 179 publications
(249 reference statements)
0
1
0
Order By: Relevance
“…Recently, studies have indicated that noncoding RNAs (ncRNAs) could regulate NAFLD progression ( Table 2 ) [ 124 , 125 , 126 ]. The ncRNAs are RNAs that do not encode functional proteins and are generally grouped based on their sizes, (1) small ncRNAs (microRNAs) and (2) large ncRNAs, including the long noncoding RNAs and circular RNAs.…”
Section: Alternative Diagnostic Toolsmentioning
confidence: 99%
“…Recently, studies have indicated that noncoding RNAs (ncRNAs) could regulate NAFLD progression ( Table 2 ) [ 124 , 125 , 126 ]. The ncRNAs are RNAs that do not encode functional proteins and are generally grouped based on their sizes, (1) small ncRNAs (microRNAs) and (2) large ncRNAs, including the long noncoding RNAs and circular RNAs.…”
Section: Alternative Diagnostic Toolsmentioning
confidence: 99%